Balance of Payments Statistics Yearbook, 2009. (Balance of Payments Statistics; Balance of Payments Statistics, 2009)
The BOPS Yearbook, usually published in December, contains balance of payments statistics for most of the world, compiled in accordance with the IMF's Balance of Payments Manual. Part 1 includes aggregate as well as detailed information in the form of analytical and standard component presentations for countries. Part 2 provides tables of data, featuring area and world totals of balance of payments components and aggregates. Part 3 presents descriptions of methodologies, compilation practices, and data sources used by individual member countries in compiling their balance of payments and international investment position statistics.